Distinctly enhanced permeability and excellent microwave absorption of expanded graphite/Fe3O4 nanoring composites. Issue 19 (15th February 2017) - Zhao, Yanting; Liu, Lin; Jiang, Kedan; Fan, Mengting; Jin, Chen; Han, Jianv; Wu, Wenhua; Tong, Guoxiu
Abstract : Distinct enhancement of permeability and permittivity is found in expanded graphite/Fe3 O4 nanoring composites caused by planar anisotropy, plasmon resonance, electromagnetic coupling, and interfacial polarization. Abstract : To break Snoek's limit and obtain high permeability, expanded graphite/Fe3 O4 nanoring composites have been synthesized via a solvothermal-surface modification-sintering approach. A series of characterizations have confirmed the formation of the composites. Studies of the influence of compound mode, Fe3 O4 shape, and filling mass fraction on the EM parameters reveal that the recombination of Fe3 O4 NRs and EG can distinctly enhance permeability and permittivity. The ε ′ and ε ′′ values of the composites are 1.5–70.0 and 4.0–858.0 times as many as EG′ and 22.2–26.0 and 214.0–611.0 times as many as Fe3 O4 NRs', respectively. Their μ ′ and μ ′′ values are around 2.8–3.0 and 2.2–100 times the Fe3 O4 NRs', respectively. This significant enhancement is caused by the synergistic effect of the planar anisotropy, plasmon resonance, electromagnetic coupling, and interfacial polarization. The EG/Fe3 O4 NR composites with a mass fraction of 10 wt% achieved the maximum R L value of −24.8 dB at 6.8 GHz and the corresponding frequency range ( R L ≤ −20 dB, 99% absorption) is 8.0 GHz. Our findings confirm that the above composites are not only excellent microwave absorbers of broad bandwidth but are also light weight and can break Snoek's limit.